If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + 3) + -10 = -2(a + 8) Reorder the terms: 6(3 + a) + -10 = -2(a + 8) (3 * 6 + a * 6) + -10 = -2(a + 8) (18 + 6a) + -10 = -2(a + 8) Reorder the terms: 18 + -10 + 6a = -2(a + 8) Combine like terms: 18 + -10 = 8 8 + 6a = -2(a + 8) Reorder the terms: 8 + 6a = -2(8 + a) 8 + 6a = (8 * -2 + a * -2) 8 + 6a = (-16 + -2a) Solving 8 + 6a = -16 + -2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2a' to each side of the equation. 8 + 6a + 2a = -16 + -2a + 2a Combine like terms: 6a + 2a = 8a 8 + 8a = -16 + -2a + 2a Combine like terms: -2a + 2a = 0 8 + 8a = -16 + 0 8 + 8a = -16 Add '-8' to each side of the equation. 8 + -8 + 8a = -16 + -8 Combine like terms: 8 + -8 = 0 0 + 8a = -16 + -8 8a = -16 + -8 Combine like terms: -16 + -8 = -24 8a = -24 Divide each side by '8'. a = -3 Simplifying a = -3
| 3(x-8)=6(x+3) | | 6(a+3)-10=-2a+8 | | 10x+224-14x=188 | | X*x*7=63 | | 11=6m-1 | | W+48=-95 | | 8t^2+4t=0 | | 1-2(6-y)=y | | 10x-8=3x+3 | | 0.2z=3z | | -21b+10a=120 | | 4y+11=13 | | 3x+16-8x=19-14x+9x-3 | | 34g+17= | | X-45=108 | | 10a-21b=120 | | 700x^2+100x-16=0 | | 65-y=256 | | y=x^4-x^3+x^2-8 | | 6s-12=42s | | 6x+3y=2x+3 | | 6x+108=11-12 | | x*x+18=22 | | 4y+11=3y+4x | | (4a^2-3a+4)-(3a^2-7a+6)= | | (3a-7)+(4a+5)= | | 2(2x+3)=3(x-10) | | (2x+4)+(8x+6)=90 | | 3n-5=-48+-4n | | 5x-3x+16=x+8 | | 0.2x-0.14=0.47 | | 13p-q-27=4p-24 |